Reversible stimulus-responsive Cu(i) iodide pyridine coordination polymer1. Issue 76 (10th October 2015) - Amo-Ochoa, P.; Hassanein, K.; Gómez-García, C. J.; Benmansour, S.; Perles, J.; Castillo, O.; Martínez, J. I.; Ocón, P.; Zamora, F.
<x xml:space="preserve">Abstract</x> A coordination polymer based on CuI double chains with substituted pyrimidine is a dynamic and reversible material very sensible to both physical and chemical stimuli.